Groupes de soutien pour aidants proches : paroles, savoirs, pouvoirs et vulnérabilités des animateurs - Émilie Charlier (Éducation et Socialisation)
Ten percent of Belgians are natural caregivers. These are confronted to major issues. Support groups are places of respite for relatives. They allow informal learning. The facilitators are confronted with the suffering of the participants on the one hand, and their own vulnerability on the other hand. This publication draws on the results of an exploratory research about the experiences of facilitators and participants in support groups for relatives of people who are confronted with life events. The article addresses informal learning, vulnerability, marginality, types of knowledge, disclosure, and speaking for vulnerable audiences. Six of the sixteen facilitators have themselves a personal experience directly linked to the theme of the group they manage.